Critical Success Factors for a Proactive Interaction Between Manufacturing and Product Development - Månsson, Christian; Fuente, Victor Romera de la (My University, 2016)
This report presents a study made at the Centre of Excellence Design for Robustness at GKN Aerospace AB (GAS) in Trollhättan, Sweden. GAS is a first-tier supplier in the global aerospace industry and manufactures components within the main product areas of civil and military aircraft as well as space propulsion including nozzles and turbines. In the increasingly competitive global market the need to identify proactive working methods within product development and ways to measure these has increased. The study has mainly addressed lessons learned and how these are brought back from the manufacturing department to the design function in order to provide a greater understanding of what manufacturing capabilities the process can handle. This research has been conducted as a case study, including thirteen interviews conducted at GAS and three benchmarking interviews in collaboration with SCA, SKF and Volvo Construction Equipment. The interviews together with a review of internal documentation and relevant literature showed that lessons learned are handled in different ways among the compared companies, that they all consider it to be an important improvement area but also that they have reached different performance levels. It was concluded that the main critical success factors that contributed to a favourable project outcome were the choice of material and the extent of the interdepartmental collaboration in terms of working proximity between the manufacturing and design departments, the extent of the collaboration between them and the empowerment of the manufacturing function within the project group. Five main recommendations were made in the study and arranged in short-, medium- and long-term according to their feasibility of implementation. First, GAS should standardize the team setup practices developed in project D to deal with design related failures. Second, GAS is advised to structure the spread of project-to-project learning around kick-off meetings, knowledge brokers, post-project reviews and lessons learned documents. Third, GAS is recommended to establish a core FMEA addressing the most critical factors for a specific manufacturing method where it can be universally applied as a starting point. Additionally, their current efforts in using QFD should be expanded to include all four houses of quality in order to fully connect the customer requirements to the process controls. Fourth, it is suggested to explore noise factors and sources of unwanted variation to deal with robustness failures. Lastly, several possibilities for improving the IT system were also mentioned, such as having a system bringing together all technical documentation in order to provide full traceability.
Keywords: Produktion; Hållbar utveckling; Industriell organisation, administration och ekonomi; Production; Sustainable Development; Industrial organisation, administration and economics